Legitimasi Keuangan dalam Perspektif Islam - Okta Leyndra Putra Santoso; Averril Corina Singgih (Jurnal Ekonomi Manajemen Akuntansi, 2024)
The prospects of Islamic banking in Indonesia, when viewed from the real sector, are quite positive. Because, the operationalization of Islamic education does not matter! interest, and the income comes from the retum for the harvest! for projects financed or margin financing the sale and purchase of goods. In this way, it can be ascertained, that theoretically Islamic banking is very interested in encouraging the progress of the nile sector. The most important thing for Islamic banking is that no matter how advanced and developed it is, it will never leave the real sector, because it is from this sector that banking activities emerge. Unlike the conventional banking system, the monetary sector has grown far away from the real sector of Inl. This is because, with interest, money has shifted from just a medium of exchange to a commodity.